To drink coffee with a ghost - Lovelace, Amanda (Lovelace, Amanda. Things that h(a)unt duology, 2019)
"You cannot have a funeral for your mother without also having a funeral for yourself." This book poses the ever-lingering question: What happens when someone dies before they're able to redeem themselves? From the bestselling & award-winning poetess, Amanda Lovelace, comes the finale of her illustrated duology, "things that h(a)unt." In the first installment, to make monsters out of girls, Lovelace explored the memory of being in a toxic romantic relationship. In to drink coffee with a ghost, Lovelace unravels the memory of the complicated relationship she had with her now-deceased mother.